Diversity of Yeasts and Their Ethanol Production at high Temperature - Vasana Tolieng, Sineenath Kunthiphun, Ancharida Savarajara, Somboon Tanasupawat (Journal of Applied Pharmaceutical Science, 2018)
Thirty one yeasts isolated from sugarcane juice and process-sediments collected from different area of sugar factory were screened for ethanol production at 40°C. The isolates were belonged to 7 genera, namely Pichia, Ogataea, Millerozyma, Meyerozyma, Candida, Kluyveromyces and Saccharomyces based on phylogenetic analysis of D1/ D2 region of the large subunit ribosomal (LSU) RNA gene. The majority of the isolates were identified as Pichia kudriavzevii (Group IB, 14 isolates), Ogataea polymorpha (Group II, 5 isolates), Kluyveromyces maxianus (Group VI, 5 isolates), Pichia manshurica (Group IA, 3 isolates), while the minor isolates were Candida tropicalis (Group V, 1 isolate), Millerozyma farinosa (Group III, 1 isolate), Meyerozyma caribbica (Group IV, 1 isolate) and Sacharomyces cereviseae (Group VII, 1 isolate). The isolates produced ethanol ranged from 2.97 to 57.10 g/L at 40°C. Isolates G3- 9(1) and G3-3(1), identified as K. marxianus and S. cerevisiae showed high potential for ethanol production, 57.10 ± 0.23 and 49.42 ± 0.34 g/L, respectively.
Keywords: Diversity,ethanol,Pichia,Kluyveromyces,Sacharomyces,thermotolerant yeasts.